Intracellular effect of β3-adrenoceptor agonist Carazolol on skeletal muscle, a direct interaction with SERCA. (May 2019) - Ramirez-Soto, Ibrahim; Rodriguez, Eduardo; Alvarez, Rocío; Quiroz, Eugenio; Ortega, Alicia
Graphical abstract: Highlights: Carazolol a known β3 agonist adrenoceptor has an unfavourable effect on isolated skeletal muscle function. Carazolol penetrates the plasma membrane and interacts directly with SERCA. Carazolol decreases slow and fast skeletal muscle force and increases muscle fatigue. Abstract: Carazolol (CZL) is a known agonist of β3 and antagonist of β1 and β2 adrenoceptors (AR), used in the animal production industry to improve meat quality by reducing animal stress and skeletal muscle (SM) proteolysis. Here we sought to better understand the direct effect CZL has on SM. We study CZL effect on calcium (Ca 2+ ) regulation by enzymatic activity kinetics of the Ca 2+ -ATPase (SERCA), in isolated sarcoplasmic reticulum (SR) from SM and on the mechanical properties of isolated muscle. In isolated SR from SM previously incubated with 0.03 mM CZL, but absent during SR isolation and during SERCA activity determination, the activity was reduced by 45%. Thermal analysis of SERCA activity with CZL shifted the transition temperature of inactivation (Ti ) from Ti  = 47 to 44 °C. When isolated SR from fast and slow SM was exposed to CZL, inhibition of SERCA occurred in a dose dependent manner. Slow and fast SM Ti of SERCA shifted to a lower temperature in the presence of CZL and a second transition appears at temperatures <40 °C. In isolated extensor digitorum longus (EDL) and soleus muscles, CZL reduces the contraction force and increases susceptibility to fatigue. However, recovery force after fatigue in either muscle was higher. Our results suggest that Carazolol penetrates the plasma membrane and interacts with SERCA, thus having an important effect on skeletal muscle function. The inhibition of SERCA may lead to a decrement in SR Ca 2+ -release promoting further failure in muscle contraction.